Cyborgization yesterday, today and tomorrow: Selected perspectives and educational contexts - Klichowski, Michał; Przybyła, Mariusz (Wydawnictwo Naukowe UAM, 2016)
In this article we attempt to show that men have aimed at cyborgizing themselves from the dawn of history. We will present selected current perspectives on the process of cyborgization that we symbolically call the restoring and extending ones. We will show selected exemplifications of cyborgizing activities and visions on the cyborgization of tomorrow. The analysis of these concepts is crucial for teachers, as they show the dichotomous relation between education and cyborgization. The dichotomy is related to the fact that on the one hand futurologists claim cyborgization is a technology of a tremendous educational potential, and on the other hand they conjecture about the concept of a world of cyborgs that exists without education.
Keywords: education; cyborgs; cyborgization; cyborg; transhumanism; ICT in education